2018
DOI: 10.1017/ice.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Medicaid Healthcare-Associated Condition Program on Mediastinitis Following Coronary Artery Bypass Graft

Abstract: Objective In 2012, the Centers for Medicare and Medicaid Services expanded a 2008 program that eliminated additional Medicare payment for mediastinitis following coronary artery bypass graft (CABG) to include Medicaid. We aimed to evaluate the impact of this Medicaid program on mediastinitis rates reported by the National Healthcare Safety Network (NHSN) compared with rates of a condition not targeted by the program (deep space surgical site infection [SSI] after knee replacement). Design interrupted time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Ten studies examined outcomes of penalty based P4P programs on the quality of surgical care [ 13 , 15 , 23 ] [ [13] , [15] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ] [ [13] , [15] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ], with the majority showing that penalty designs were effective [ 24 , 26 , 27 , 29 , 30 ]. Although six out of 10 studies reported improved quality in surgical care, we conclude that one study did not congruently show a positive effect of P4P programs due to lack of comparison to the pre-policy period [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies examined outcomes of penalty based P4P programs on the quality of surgical care [ 13 , 15 , 23 ] [ [13] , [15] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ] [ [13] , [15] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ], with the majority showing that penalty designs were effective [ 24 , 26 , 27 , 29 , 30 ]. Although six out of 10 studies reported improved quality in surgical care, we conclude that one study did not congruently show a positive effect of P4P programs due to lack of comparison to the pre-policy period [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, financial incentives to reduce healthcareassociated complications have gained momentum, resulting in manifold 'pay for performance' strategies; however, parts of such schemes may not be as effective as expected. 8 In our study, the prospective DRG payment system indirectly penalized hospitals for complications without having to rely on hard-to-collect performance indicators.…”
Section: Discussionmentioning
confidence: 97%
“…Previously implemented CMS policies and the current VBIPs showed no evidence in reducing the rates of central catheter-associated bloodstream infections, surgical site infections after colon surgical procedures and abdominal hysterectomy procedures, 16 catheter-associated urinary tract infections, 17,18 and mediastinitis following coronary artery bypass graft surgery. 19,20 There are several possible explanations for the apparent association between VBIPs and the decline in HO-CDI rates. First, this could reflect a commitment by health care organizations in reducing the infection rates by taking increasingly aggressive measures to prevent CDI.…”
Section: Discussionmentioning
confidence: 99%